Manipulation of Deformable Linear Objects Enabled by Sound-event Classification in the Manufacturing Environment - Nguyen, Huong Giang; Javaheri, Negin; Franke, Jörg (2023 IEEE International Conference on Industrial Engineering and Engineering Management, IEEM 2023, 2023)
Automated handling of deformable linear objects (DLO), specifically wires, is challenging due to their physical and geometric properties. Manufacturing companies handling wires mainly rely on manual work with operators to produce wiring systems. To address the research gap for automated wire handling solutions, this article addresses the human-robot co-manipulation of DLO and focuses on robot hearing for process monitoring. The focus is on the handling task of DLO insertion. Robot hearing in the manufacturing environment was realized through an acoustic sensor and sound-event classification. The paper outlines the collaborative robot system and data processing pipeline for audio data classification. The goal is to assess the process of DLO insertion regarding success and failure. The experiments were conducted for an automotive use case. Data collection, pre-processing, and processing are presented and experiments were conducted to evaluate the proposed solution. The experimental findings show that high accuracies for sound-event classification can be achieved and enable reliable and monitored robotic DLO handling.
CRIS-Team Scopus Importer:2024-12-16